2016
DOI: 10.1111/jrh.12206
|View full text |Cite
|
Sign up to set email alerts
|

Veteran Use of Health Care Systems in Rural States: Comparing VA and Non‐VA Health Care Use Among Privately Insured Veterans Under Age 65

Abstract: Over half of working-age veterans enrolled in VA and private insurance used services in both systems. Care coordination efforts across systems should include veterans of all ages, particularly rural veterans more likely to be dual users, and better methods are needed to identify veterans with private insurance and their private providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…5,6 Studies characterizing Veterans' healthcare utilization indicate that as many as half of Veterans rely on both VA and non-VA sources of care, with older and more rural Veterans more likely to be dual users. [7][8][9] Patients make complex decisions regarding healthcare seeking based on their access to care, perceptions of care, prior utilization, satisfaction, quality, and outcomes [10][11][12] and there is growing recognition of the need to assess patient experiences of cross-system care as a means of evaluating its coordination and quality. 13 Both VA and non-VA providers have reported significant frustration with crosssystem care coordination, particularly related to barriers to information exchange and a lack of role clarity and care tracking.…”
Section: Current Evidence On Cross-system Care Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Studies characterizing Veterans' healthcare utilization indicate that as many as half of Veterans rely on both VA and non-VA sources of care, with older and more rural Veterans more likely to be dual users. [7][8][9] Patients make complex decisions regarding healthcare seeking based on their access to care, perceptions of care, prior utilization, satisfaction, quality, and outcomes [10][11][12] and there is growing recognition of the need to assess patient experiences of cross-system care as a means of evaluating its coordination and quality. 13 Both VA and non-VA providers have reported significant frustration with crosssystem care coordination, particularly related to barriers to information exchange and a lack of role clarity and care tracking.…”
Section: Current Evidence On Cross-system Care Coordinationmentioning
confidence: 99%
“…However, higher levels of care coordination may be warranted due to greater healthcare need (e.g., multiple comorbidities, advanced or more severe conditions), limited personal resources, and frequent cross-system use. 7,[21][22][23] In addition to PACT, VA Office of Community Care has developed a triage tool to differentiate Veterans with low, moderate, or high needs for coordination to facilitate coordination and navigation within and outside the VA. This tool also helps in documenting the intensity ("dosage") of coordination delivered.…”
Section: Identifying Veterans Who Benefit Most From Care Coordinationmentioning
confidence: 99%
“…However, dual use is an ongoing coordination issue for VA facilities, where Veterans who are ‡65 years of age are eligible for VA services and may also use Medicare to access care and cover health expenses. Recent studies have also shown that dual use is common among working-age Veterans (those under age 65) to address both inpatient and outpatient care needs, [9][10][11] particularly in rural areas. One study found that 54% of rural dwelling Veterans used both VA and private insurances.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that 54% of rural dwelling Veterans used both VA and private insurances. 9 Furthermore, higher risk Veteran patients (i.e., those with higher Hierarchical Condition Category [HCC] scores) are more likely to be dual users. 10…”
Section: Introductionmentioning
confidence: 99%
“…Veterans with complex health care needs increasingly utilize both the Veterans Health Administration (VA) and non-VA hospitals [13]. Roughly 50% of Veterans are dual-users [24], receiving care from both VA and non-VA hospitals. With the addition of the VA’s Mission Act (previously the Choice Act), access to community care will likely increase.…”
Section: Introductionmentioning
confidence: 99%